PENGGUNAAN KAPASITOR BANK UNTUK MEMPERBAIKI FAKTOR DAYA DAN MENGURANGI RUGI-RUGI DAYA MENGGUNAKAN FUZZY LOGIC CONTROLLER DI QUEST HOTEL KUTA BADUNG - Wiadnya Wiantara, I Dewa Gede; Mataram, I Made; Manuaba, Ida Bagus Gd. (Program Studi Teknik Elektro UNUD, 2020)
Quest Hotel Kuta is a place of business engaged in lodging services. To support operational needs, the hotel uses electrical equipment, most of which are inductive. The use of high inductive loads can produce high reactive power, depending on the power factor because the active power obtained from the installed power will be less. Based on the measurement results at Quest Hotel Kuta the measured power factor is 0.70, while PLN charges the excess cost of kVARH to the customer if the average power factor is less than 0.85. To be able to improve the low power factor can be done by using a capacitor bank, the capacitor uses the reactive power required at the inductive load. Changing the power factor in consumers can change. To equalize the power change factor, the capacitor bank is assembled to work multiple steps / multi steps. Multi-step capacitor banks consist of several capacitors with the same or different capacities. Based on the results of measurements before using the fuzzy logic method, the obtained power factor is 0.70 to 0.74 while the capacitors are installed from 12.5 kVAR to 25 kVAR. After using the fuzzy logic controller method the power factor obtained is 0.80 to 0.87 and capacitors using the 13.1 kVAR to 22.4 kVAR method. Whereas the power losses before using the fuzzy logic controller method are 26220.5 watts. After using the fuzzy logic controller method, the power losses incurred were 23214.45 watts.